Maxillary Protraction: A Bibliometric Analysis - Minmin Si; Zhaonan Hao; Hao Fan; Huan Zhang; Rui Yuan; Zhiyuan Feng (Elsevier, 2023)
Objectives: The aim of this analysis was to investigate the historical development, current status, and research hot spots related to maxillary protraction in the treatment of maxillary hypoplasia. Methods: The term "TS = maxillary protraction" was used to search for articles in the Web of Science Core Collection at the library of Capital Medical University. The results were analysed using CiteSpace6.2.R1 software, including the examination of annual publication trends and analysis of author, country, institution, and keywords. Results: A total of 483 papers were included in this study. The annual publications showed an overall increasing trend. The top 5 authors with the most published papers were Lorenzo Franchi, Tiziano Baccetti, Seung-Hak Baek, Paola Cozza, and U Hagg. The top 5 countries with the highest publication counts were the US, Turkey, South Korea, Italy, and China. The top 5 institutions in terms of the number of published papers were the University of Florence, the University of Michigan, Kyung Hee University, Seoul National University, and Gazi University. The top 3 journals with the most citations were the American Journal of Orthodontics and Dentofacial Orthopedics, Angle Orthodontist, and the European Journal of Orthodontics. Furthermore, "Maxillary protraction," "Class III malocclusion," and "Maxillary expansion" were the most common keywords. Conclusions: The effective age range for maxillary protraction has been expanded with the introduction of skeletal anchorage and the combination of maxillary expansion and protraction. Skeletal anchorage offers significant advantages over dental anchorage, but there is a need for further research to further substantiate its stability and safety. In recent years, the positive effects of maxillary protraction on the nasopharyngeal area have been well established, but its impact on the oropharyngeal area remains a topic of debate. Therefore, it is crucial to conduct further investigations into the effects of maxillary protraction on the oropharyngeal area and explore the factors that influence different outcomes.